If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 = 2 + 6x + 10 Reorder the terms: 12 + 6x = 2 + 6x + 10 Reorder the terms: 12 + 6x = 2 + 10 + 6x Combine like terms: 2 + 10 = 12 12 + 6x = 12 + 6x Add '-12' to each side of the equation. 12 + -12 + 6x = 12 + -12 + 6x Combine like terms: 12 + -12 = 0 0 + 6x = 12 + -12 + 6x 6x = 12 + -12 + 6x Combine like terms: 12 + -12 = 0 6x = 0 + 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3.2s-5=5-18s | | 6x-2(X+4)=4(5+x) | | 3a-16=-31 | | (5y+1)(5+y)=0 | | 5x^3+2x^2=20x+8 | | 3.2s-5=5-18 | | 3x+u=7 | | 3a-16=31 | | 5(1-x)=-5(6x-6) | | 223=6*x+7 | | 12.6=x*40 | | 9(-10+x)-5(2x+9)=4-x+11 | | 5x-50=15 | | -19y=2x+.05 | | 6x+2+2-3x=-4(6x-3)+3(-x-3) | | 6a+17=-1 | | -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 |